Dental Resorption without Hypercementosis in Horses: Case Reports and Discussion - Arnbjerg, Jens (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
A horse with poor body condition, periodontal infection and pain around the mandibular incisors with only fragments of the teeth left was studied and radiographed before and after surgery during a 17-month period. Another horse with a mandibular fracture and fractured teeth were followed by yearly radiographed for a period of 9 years to observe the resorption of parts of the roots. The horse had no clinical problems at all related to the mandibular and teeth fractures. The aim of this study was to show that resorption of the teeth in the horse is not always related to hypercementosis, and clinical symptoms are often related to infection around the teeth. A fractured root does always result in clinical symptoms. The resorption rate seems depending on the status of periodontal membrane. If the membrane is intact the resorption process is prolonged (several years). If the membrane is demolished the resorption is quite rapid (about a year). If there is infection even more rapid.